2014
DOI: 10.1016/j.rboe.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after total knee arthroplasty: systematic review

Abstract: ObjectiveTo review the literature on quality of life among patients who underwent total knee arthroplasty (TKA) and assess the impact of various associated factors.Methodsthis was a systematic review of the literature in the Medline, Embase, Lilacs and SciELO databases, using the terms: TKA (total knee arthroplasty); TKR (total knee replacement); quality of life; and outcomes. There were no restrictions regarding study design.Results31 articles addressing this topic using various quality-of-life evaluation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
66
2
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 40 publications
8
66
2
7
Order By: Relevance
“…Corroborating to the findings of this study, similar research showed evidence that BMI is a predictor for THA positive results (Slaven, ) and showed predominant mean age of patients around 59.17 ( SD = 14.7) (Pinto et al., ). Literature suggests as negative factors associated to the postoperative recovery comorbidities, obesity and advanced age (Silva, Santos, Carvalho Júnior, & Matos, ), though this study showed a sample with opposite factors.…”
Section: Discussioncontrasting
confidence: 53%
“…Corroborating to the findings of this study, similar research showed evidence that BMI is a predictor for THA positive results (Slaven, ) and showed predominant mean age of patients around 59.17 ( SD = 14.7) (Pinto et al., ). Literature suggests as negative factors associated to the postoperative recovery comorbidities, obesity and advanced age (Silva, Santos, Carvalho Júnior, & Matos, ), though this study showed a sample with opposite factors.…”
Section: Discussioncontrasting
confidence: 53%
“…Thus, abnormal flexion-extension moment patterns are thought to be associated with aberrant flexor and extensor muscle activity [3] . While successful outcomes have been reported following TKR [4] , significant functional deficits remain post-surgery [5] . In fact, approximately 25% report a fall within the year following TKR surgery [6] .…”
Section: Introductionmentioning
confidence: 99%
“…A doença articular degenerativa, osteoartrose, é, no geral, a principal causa de deficiência física entre idosos. A dor e a limitação funcional provocadas por essa condição, especialmente nos membros inferiores, apresentam forte correlação com a redução na QV dessas pessoas 6,7 .…”
Section: Introductionunclassified
“…Os métodos atuais de avaliação dos resultados da ATJ são baseados principalmente em sinais e sintomas clínicos, no exame físico e na avaliação radiográfica. Esse tipo de avaliação não contempla todos os aspectos do tratamento, já que não é capaz de detectar as reais necessidades e expectativas do paciente, tais como mudanças na QV, nas relações sociais e no seu meio ambiente 6,[8][9][10][11] .…”
Section: Introductionunclassified